The risks of playing for time in Algeria: Internal strife over key choices after the presidential election - Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2014)
With the re-election of the seriously ailing President Abdelaziz Bouteflika, Algeria's power elites have gained time to reach agreement over the general outline of the post-Bouteflika era. Despite rising fears within the regime of social unrest in the absence of fundamental reforms, precious few among the political, military and business elites are in fact willing to risk reforms that would threaten their sinecures and status. Structural factors are also obstacles to change. However, the strategy of playing for time without tackling the issue of substantial reforms is probably riskier in the long term than a policy that allows for such reforms. Reform deadlocks in the strategic oil and gas sector, socioeconomic and ethnic conflicts and regional security challenges demand that key choices be made soon. Europe may not have much influence over Algeria's internal decision-making processes, but a purely stability-orientated policy aligned with European security and energy interests is short-sighted. (SWP Comments)
Keywords: 320